Properties Of Ultra-High Performance Concrete (Uhpc) Containing Modified Aggregate System And Chemical Additives - Saw, Yoong Kang (2024)
Ultra-high performance concrete's (uhpc) higher strength, durability, and high ductility performance make it a versatile construction material. However, it also poses sustainability problems due to its high cement content and quartz sand-intensive consumption during the manufacturing phase of uhpc. Coal bottom ash (cba) is a possible alternative to aggregate due to its increasing output from coal power stations and the scarcity of high-quality natural sand. The purpose of this study is to determine an efficient approach to incorporate cba as an aggregate replacement in uhpc composites. Nanomaterial technologies, such as nano calcium silicate hydrate (c-s-h), were used as an additive to improve the mechanical, durability, and microstructure parameters of uhpc containing cba aggregate. The binder phase of all uhpc mixes was ternary blended mix optimised with a combination of opc, ground granulated blast furnace slag (ggbs) and silica fume (sf) at the ratio of 15:4:1. Steel fibre reinforcement is found to be optimum at 2% to the binder volume. According to findings, uhpc mix with graded cba as the aggregate replacement achieved better strength and durability development due to a denser microstructure. All uhpc mixes had a reduction in mechanical and durability performance when cba was used as the aggregate replacement. Among all uhpc mixes with different levels of cba as an aggregate replacement,